BENTUK, FUNGSI DAN MAKNA TINDAK TUTUR ILOKUSI DALAM KOMUNIKASI ANTARA IBU KOS DAN ANAK KOS DI LINGKUNGAN KOS BERLIAN (KAJIAN PRAGMATIK) - De Jesus, Maria; Djuli, Labu; Makan Malay, Narantoputrayadi (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This research aims to describe the form, function and meaning of illocutionary speech acts in communication between the landlady and the boarders in the Berlian Boarding House environment. Communication established in the boarding house environment is not only functional, but also reflects complex and dynamic social relationships. This research uses descriptive qualitative approach with observation and interview method to the landlady and some boarders who live in Berlian Boarding House. The results show that there are five types of illocutionary speech acts used, namely assertive, directive, commissive, expressive and declarative. Assertive speech acts dominate in the form of orders or appeals from boarding mothers to boarding students, while boarding students often use expressive speech acts as a form of respect and courtesy. 2. The functions of illocutionary speech acts in the communication between the boarding house mother and the boarding house children in the Berlian boarding house environment include the functions of telling, boasting, asserting, stating, admitting, complaining, reporting, showing, mentioning, ordering, requesting, prohibiting, advising, pleading, offering, promising, refusing, thanking, apologizing, congratulating, granting and allowing. The function of these speech acts is not only as a means of communication, but also as a means of maintaining harmony and building positive social relations between boarders. The meaning of speech acts that arise is strongly influenced by the context of the situation, social relations, and speech culture that applies in the boarding house environment.